Gemcitabine-Induced Pulmonary Toxicity in a Patient with Pancreatic Cancer - Hiraya, Daigo; Kagohashi, Katsunori; Sakamoto, Naoya; Kondo, Tadashi; Satoh, Hiroaki (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Chest CT showing bilateral diffuse ground-glass opacities in both lungs.